Citrus Leafminer Parasitoid, Ageniaspis citricola Logvinovskaya (Insecta: Hymenoptera: Encyrtidae) - Alison Walker; Marjorie A. Hoy (EDIS)
The encyrtid parasitoid Ageniaspis citricola was first imported into Florida from Australia in 1994 in a classical biological control program against the citrus leafminer, Phyllocnistis citrella Stainton (Hoy and Nguyen 1994a). A second strain of Ageniaspis citricola was introduced into Florida from Taiwan in 1997, although there is no evidence that this second strain ever established (Hoy and Nguyen 1997). The citrus leafminer was first detected in Florida in 1993, and quickly spread throughout all 860,000 acres of citrus, posing a serious threat to the state's citrus industry. The population of A. citricola from Australia quickly established and dispersed throughout the state, reaching parasitism levels near 100% in some areas (Hoy et al. 1995ab, Knapp et al. 1995, Bullock et al. 1996, Pomerinke and Stansly 1998). Ageniaspis citricola is consistently the dominant parasitoid of citrus leafminer in Florida. This document is EENY-285 one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2003.